Numerical analysis of dynamic properties of wrinkled thin membranes. Issue 8 (9th April 2020) - Wang, Xiaofeng; Chu, Haoyue; Yang, Qingshan
Abstract : Purpose: This paper aims to numerically study the effects of boundary conditions, pre-stress, material constants and thickness on the dynamic performance of a wrinkled thin membrane. Design/methodology/approach: Based on the stability theory of plates and shells, the dynamic equations of a wrinkled thin membrane were developed, and they were solved with the Lanczos method Findings: The effects of wrinkle-influencing factors on the dynamic performance of a wrinkled membrane are determined by the wrinkling stage. The effects are prominent when wrinkling deformation is evolving, but they are very small and can hardly be observed when wrinkling deformation is stable. Mode shapes of a wrinkled membrane are sensitive to boundary conditions, pre-stress and Poisson's ratio, but its natural frequencies are sensitive to all these five factors. Practical implications: The research work in this paper is expected to help understand the dynamic behavior of a wrinkled membrane and present access to ensuring its dynamic stability by controlling the wrinkle-influencing factors. Originality/value: Very few documents investigated the dynamic properties of wrinkled membranes. No attention has yet been paid by the present literature to the global dynamic performance of a wrinkled membrane under the influences of the factors that play a pivotal role in the wrinkling deformation. In view of this, this paper numerically studied the global modes and corresponding frequencies of a wrinkled membrane and their variation with the wrinkle-influencing factors. The results indicate that the global dynamic properties of a wrinkled membrane are sensitive to these factors at the stage of wrinkling evolution.